Karakteristik Bahasa Parempuan pada Tokoh Utama dalam Novel Perempuan Dititik Nol Karya Nawal El Saadawi - Saputra, Eko Suzi; Rosyidah, Neneng Aida (Universitas Muhammadiyah Gorontalo, 2023)
Cultural factors that cause differences in language characteristics between men and women are an interesting thing to study. The country that is still very thick with its patriarchal culture is the State of Egypt, which causes differences in language characteristics between men and women. The novel Woman at Point Zero by Nawal El Saadawi is based on a true story of a woman who fought against patriarchal culture in Egypt and was about to be executed for killing someone. The purpose of this writing is to find out the characteristics of women's language in Nawal El Saadawi's women's novel at zero point based on Robinn Lakoff's theory of women's language. The analytical method used in this research is descriptive analysis method. With this method, the researcher analyzes the choice of each word used by the main female character in the novel Woman at Point Zero, so that the language characteristics of the main female character in the film can be revealed. While the method used to collect data in this study is the technique of reading and noting on primary data sources. . In this study, 4 characteristics of women's language were found in the novel Woman at Point Zero by Nawaal El Saadawi based on Robin Lakoff's theory, namely: empty adjectives, hedge, intensifier, avoidance of strong swear words. The use of these linguistic characteristics cannot be separated from the existing patriarchal culture in Egypt. and experienced by the main character in the novel, causing women to be very careful in their speech and often use intensifiers to emphasize their utterances so that their interlocutors understand the meaning of their speech. This novel clearly explains the condition of women who are still second in the country.